Odpowiedzi

2010-03-10T19:06:07+01:00
A)(5x+4xy+5y)-(2x-xy-3y)+(-x+2xy+y)=
5x+4xy+5y-2x+xy+3y-x+2xy+y=
2x+9y+7xy

b)-(2a+3ab)-(2b-ab)+(5a-2ab)-(-5b+4ab)=
-2a-3ab-2b+ab+5a-2ab+5b-4ab=
3a+3b-8ab
c)(2x-3)-(xDP2-3x+1)+(3xDP2-6x-5)=
2x-3-x²+3x-1+3x²-6x-5=
2x²-x-9
1 5 1
2010-03-10T19:08:42+01:00
A)(5x+4xy+5y)-(2x-xy-3y)+(-x+2xy+y)=
5x+4xy+5y-2x+xy+3y-x+2xy+y=
2x+9y+7xy

b)-(2a+3ab)-(2b-ab)+(5a-2ab)-(-5b+4ab)=
-2a-3ab-2b+ab+5a-2ab+5b-4ab=
3a+3b-8ab

c)(2x-3)-(xDP2-3x+1)+(3xDP2-6x-5)=
2x-3-x²+3x-1+3x²-6x-5=
2x²-x-9

Buziaczki :))
1 4 1